1998
DOI: 10.1016/s0014-5793(98)00039-8
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol binding to cell surface raises cytosolic free calcium in T cells

Abstract: The Fura-2 method is used to examine a possible action of 17L L-estradiol (E P ) on [ influx and Ca P+ release from intracellular stores is also inducible by plasma membrane impermeable E P conjugated to BSA. E P -BSA-FITC binds to the surface of T cells of both the CD4 + and CD8 + subset. Our data suggest a novel E P -signalling pathway in T cells which is not mediated through the classical nuclear estrogen receptor response but rather through putative plasma membrane receptors for E P .z 1998 Federation of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 32 publications
9
88
0
Order By: Relevance
“…To date, the precise location of membrane-associated ER is a matter of debate, i.e., it has not been determined whether the membraneassociated ER binding site is on the inner or outer leaflet of the plasma membrane. Several investigators, using a variety of ER-specific antibodies in intact, nonpermeabilized cells, have hypothesized that the expression of ER occurs at the external leaflet of the cell membrane (38)(39)(40)(41)(42)(43)(44)(45). Conversely, other research groups have pointed to the cytoplasmic tail of membrane-associated ER as a key functional domain (8).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the precise location of membrane-associated ER is a matter of debate, i.e., it has not been determined whether the membraneassociated ER binding site is on the inner or outer leaflet of the plasma membrane. Several investigators, using a variety of ER-specific antibodies in intact, nonpermeabilized cells, have hypothesized that the expression of ER occurs at the external leaflet of the cell membrane (38)(39)(40)(41)(42)(43)(44)(45). Conversely, other research groups have pointed to the cytoplasmic tail of membrane-associated ER as a key functional domain (8).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of gene transcription by estrogen requires ER dimerization and binding to an estrogen response element (ERE), followed by activation of transcription factors and cofactors (58). ERs are expressed in a variety of immunocompetent cells, including T cells and macrophages (21,59,60), and EREs have been identified in a number of immunologically relevant genes. For example, an ERE has been mapped to the 5Ј-flanking sequence of the IFN-␥ gene, and estrogen has been shown to induce transcription of genes containing this ERE (61).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mammalian mast cells, T and B cells and macrophages shows membrane AR and membrane ER (Benten et al, 1998(Benten et al, , 2001(Benten et al, , 2002Zaitsu et al, 2007). A membrane ER (Pang et al, 2008) and a membrane AR (review in Thomas et al, 2006) have recently been cloned and characterized in atlantic croaker, although nothing is known about membrane AR in fish immune tissues.…”
Section: Sex Steroid Hormones As Regulators Of the Immune Responsementioning
confidence: 99%
“…In the gilthead seabream, lymphocytes only express the ER gene (Liarte et al, 2011b). In mammals, however, B lymphocytes express both ER and ER genes, while there is debate as to whether or not T cells contain classical nuclear ER (Benten et al, 1998;Harkonen & Vaananen, 2006). In vitro functional assays demonstrated that 17-estradiol stimulates lymphocyte proliferation (Cook et al, 1994).…”
Section: Lymphocytesmentioning
confidence: 99%